ELEMENTS OF FRICTION INTERACTION AND INCREASE OF THE LOAD OF THE WHEEL-RAIL PAIR - Malinovskiy, Yuriy; Nevljudov, Igor; Tsvirkun, Sergij; Vlasenkov, Dmitro; Tkachenko, Andrij; Oliinyk, Svitlana (Problems of Friction and Wear, 2023)
The loading property of the wheel-rail pair is one of the main factors affecting the rational design of vehicles of various technical purposes. Based on the experience of railway transport, there is an idea that with an increase in the vertical load on the wheel and, accordingly, the rail, the durability of this pair decreases in proportion to the increase in load. However, the observations of some researchers outside of the steam load suggest that within a certain range of increasing working vertical loads on the wheel (pair of wheels) there may be a slight increase in steam strength. These data, as it were, were not refuted and did not receive theoretical confirmation. For example, from the results of solving Hertz’s contact problem on the rolling of an elastic cylinder in a strip of the same material (or closed in the properties), where a direct proportion was established between the load current and New stresses in the materials of the interacting parts, and therefore proportionally reduce the durability of the pair. In contrast to the mentioned results, when setting the task, an assumption was made that the wheel and rail materials were not uniform throughout their thickness. The outer thin layers of the material under the influence of vertical and tangential adhesion loads receive surface hardening and are therefore harder, the anisotropy of the material properties of the parts in their thickness is manifested in this. In this work, an analogy was used between the task of rolling a wheel on a rail and the tasks of metal pressure processing for the cases of cold and hot rolling, running -in and other types of surface treatment of pressure parts. For these technological processes, with an increase in vertical load, significant structural changes occur in the crystal lattices of the surface layers, which can "increase", can be interpreted as a change in the modulus of elasticity and hardness indicators of the surface layers. As the depth of the stamped layer increases, the values of yield strength, strength and durability of these thin layers increase. Therefore, given this analogy, the resistance to force and wear of the corresponding pair is significantly increased during operational production within the limits limited by the so-called "critical" thickness of the stamped layer. If this thickness is exceeded, further intensive wear and further destruction of the interacting parts should follow. However, the surface strength of the parts of the wheel-rail pair can be significantly increased using static and dynamic hardening methods even before the operation of these pairs on vehicles.